Kemurungan dan Harga Diri di Kalangan Murid-Murid 'Latchkey' di Sekolah Kebangsaan di Pantai Timur Semenanjung - Yusoff, Emi Yusmidar Md; Mahamood, Yahaya (ANIMA Indonesian Psychological Journal, 2005)
The relation between depression and self-esteem among average students reveals a negative correlation, though environmental factors are sometimes taken into account. This study examined children with rather "weary” conditions and because of that were studied to confirm the correlation between self-esteem and depression among latchkey children who were assumed having various problems. Controlled variables are gender, family's economic condition, and educational status. Students of an elementary school was randomly and stratified sampled to fill in3 forms: Children's Depression Inventory, Cooper smith Self-Esteem Inventory, and Self-Monitoring questionnaire. Pearson correlation reveals a negative correlation between depression and self-esteem among the latchkey children, although the percentage and proportion does not differ from non-latchkey children in other studies. The negative corelation was not affected by gender, family economic condition, and educational status, which were supported by t-test and ANOVA. This condition was supported by descriptive analyses and observation during the study, paying attention to the social support factors of the studied area. Hubungan antara kemurugan dan harga diri di kalangan murid biasa jelas memperlihatkan kenegatifan korelasi sekalipun faktor-faktor lingkungan kadang-kadang diperhitungkan. Kajian ini meninjau kanak-kanak yang dikatakan agak dalam “kepayahan” dan atas alasan itu dicoba dikonfirmasi sekali lagi hubungan harga diri dan kemurungan terutama di kalangan kanak-kanak yang tinggal di rumah tanpa pendampingan orang dewasa (latchkey) yang berkemungkinan besar menghadapi berbagai masalah. Beberapa variabel yang diperkirakan memberi kesan telah diuji adalah gender, taraf ekonomi keluarga dan perbedaan tahap pendidikan. Sejumlah murid sekolah rendah (N=150) telah dipilih secara acak berstrata untuk mengisi 3 borang angket: Children's Depression Inventory, Coopersmith Self-Esteem Inventory dan Maklumat Diri. Korelasi Pearson menunjukkan adanya korelasi negatif diantara kemurungan dengan harga diri di kalangan murid yang tinggal di rumah tanpa pendampingan orang dewasa tetapi persentase atau proporsinya tidak berbeda bila dibandingkan dengan pelajar lainnya dalam kajian-kajian sebelum ini. Hubungan negative ini tidak dipengaruhi faktor-faktor gender, taraf ekonomi keluarga dan tahap pendidikan yang dikuatkan dengan uji-t dan ANOVA. Kedudukan ini didukung oleh analisis deskripsi dan observasi selama kajian dijalankan dengan memperhatikan peranan faktor dukungan sosial masyarakat di kawasan kajian.